Hellenic Places: Hermoupolis - Margaritis, Charalambos (My University, 2021)
The city of Hermoupolis, capital of Syros is located at the center of the Cyclades, in the Aegean Sea, in Greece. In its history one can find all the elements that shaped contemporary Greece. This is an animated documentary telling its story.
Keywords: Documentary; Animated film